(untitled) (Physical Education, Health and Social Sciences, 2025)
Women face a multitude of challenges in their daily lives as housemaids. These challenges include pathetic work conditions, unequal wages, and maltreatment of women, social pressure, and violence. This study is primarily conducted to ascertain the perennial challenges of Women in the rural Punjab, the largest province in Pakistan in terms of population. To conduct this study, a qualitative survey was taken and in-depth interviews were conducted with the housemaids in rural Punjab. The findings of the study were that the women in rural Punjab faced immense issues, ranging from wage disparities, and unfriendly work conditions that violate fundamental human rights. It was discovered after in-depth interviews that housemaids face lower wages, physical and verbal abuse, social pressure, sexual harassment, and exploitative and poor work conditions. These issues are faced in daily routine in most of the rural Punjab. There is a dire need for awareness to address the issues of labor at the local and national level. Labors should be organized at the local level, forming their unions at every level to identify and address their issues. After careful examination of the study, it can be recommended that the condition and domestic labor should be improved through policy-level intervention at both international and domestic levels.